Pabrikasi Membrane Electrode Assembly Menggunakan Metode Decal Transfer Dengan Variasi Suhu Hot Press Terhadap Katalis Platina-Titanium Dioksida Didukung Vulcan XC-72 - Fauzi1, Ilham; Joni, Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstract The increasing use of fossil fuels in various countries, especially in the automotive sector, is one of the causes of the energy crisis and air pollution. Efforts that can be made are to switch from fossil fuels to new and renewable energy. Several new and renewable energies have been widely developed, for example hydrogen energy. An example of the application of hydrogen energy is fuel cells. The type of fuel cell that can be used in the automotive sector is the proton exchange membrane fuel cell (PEMFC). PEMFC has the most important component, namely the membrane electrode assembly (MEA). The complicated fabrication of MEA and its expensive materials are the causes of problems that must be solved. One solution is to substitute platinum with titanium dioxide. The decal transfer method is widely used because it can increase the contact of the ionic catalyst to the membrane. In this study, MEA fabrication was carried out using the decal transfer method by varying the hot press temperature, namely 40 ?C, 60 ?C, and 80 ?C to determine the optimal temperature and performance of the MEA produced using MEA performance testing. The thickness of the catalyst used was 30 ?m and the thickness of the MEA was set at 140 ?m. From the test results, it was obtained that MEA with temperature variations of 40 ?C and 60 ?C produced the smallest voltage, namely 0.1 ?V and 0.2 ?V, while at a temperature of 80 ?C the voltage produced reached its largest voltage, namely 0.4 ?V. So, it can be concluded that the best temperature is 80 ?C Keywords: PEMFC, MEA, Hot press temperature